Equitable food systems in practice? The case of smallholders’ marketing of legumes in Malawi - Kakwera, Mayamiko Nathaniel; Kambewa, Daimon; Haug, Ruth (Frontiers in Sustainable Food Systems, 2025)
We assess how Malawian smallholder farmers engage with legume markets in Dowa district and how these markets function to either support or hinder equitable livelihoods. The analysis is based on mixed methods, including surveying households that grow and sell soybeans, groundnuts, and common beans, farmer focus group discussions, in-depth interviews with traders and processors, and key informant interviews with market facilitatory actors. Our theoretical framework draws from food systems, equity, and farmer typology. We found that most farmers in Dowa rarely sell their legumes in the markets they perceive as lucrative namely, to large-scale traders and processors, as these markets require substantial volumes per sale and are often located far from the farms. The state-run Agricultural Development Market Corporation turned out to be ineffective. Yet, it remains the farmers’ preferred market option due to its history of adhering to floor prices and using accurate scales. Village and mobile traders are the main commodity off-takers, despite farmers reporting that they buy below the set floor prices and use inaccurate scales. In turn, the village and mobile traders face challenges in dealing with smallholder farmers, such as commodity adulteration, sparsely located farmers, and the distances travelled to gather significant volumes of commodity. Large-scale traders and processors provide village and mobile traders with the most viable offloading options. Village, district, and large-scale traders all reported declining market opportunities driven by unfavourable trade policies, which are seen to be lobbied by powerful actors in the legume supply chains; ultimately this affects how traders interact with farmers. Many smallholder farmers in the “dropping out” and “hanging in” categories are indebted and engage in advance crop sale debts, which seems to contribute towards inequity rather than equity. Despite the prevalence of market policies to protect smallholder farmers from exploitation, implementation is challenging, thus rendering market control on paper and market liberalisation in practice.